Policies supporting surplus personnel in the rearrangement of administrative units: current situation and solutions to improve implementation effectiveness - To Trong Manh (Journal of State Management, 2025)
The rearrangement of district- and commune-level administrative units under Resolution No. 37-NQ/TW dated December 24, 2018 of the Politburo marks a strategic step in reforming the state apparatus toward a more streamlined, effective, and efficient structure. Notably, since July 1, 2025, with the implementation of theGovernment’s Resolution No. 74/NQ-CP dated April 7, 2025 and the National Assembly’s Resolution No. 202/2025/QH15 dated June 12, 2025, the streamlining of the apparatus has undergone significant changes,leading to an objective and inevitable consequence: a surplus of cadres, civil servants, and non-professional personnel. Formulation and implementation of policies to support surplus personnel have therefore become a key task to ensure social security, foster consensus, maintain internal stability, and preserve trust within the workforce. This article analyzes the significance of such policies in the context of administrativerestructuring, identifies existing shortcomings in their implementation, and proposes solutions to enhance their effectiveness and utilize human resources after mergers, toward a humane, sustainable, and comprehensive administrative reform process.